Activation of Different Heterodimers of TLR2 Distinctly Mediates Pain and Itch. (1st March 2020) - Wang, Ting-Ting; Xu, Xian-Yun; Lin, Wei; Hu, Dan-Dan; Shi, Wu; Jia, Xin; Wang, Hui; Song, Ning-Jing; Zhang, Yu-Qiu; Zhang, Ling
Highlights: TLR2 is expressed in different primary sensory neurons in TG and DRG. TLR2 is involved in inflammatory pain, acute and chronic itching. Activation of TLR2/TLR1 or TLR2/TLR6 produces distinct itch and pain behaviors. Activation of TLR2 increases [Ca 2+ ]i in DRG neurons via TRPV1 and TRPA1 channels. Abstract: Toll-like receptors (TLRs) have been implicated in pain and itch regulation. TLR2, a TLR family member that detects microbial membrane components, has been implicated in pathologic pain. However, the role of TLR2 in pruritic and nociceptive responses has not been thoroughly investigated. In this study, we found that TLR2 was expressed in mouse dorsal root ganglia (DRG) and trigeminal ganglia (TG) neurons. Itch and pain behaviors, including histamine-dependent and histamine-independent acute itching, acetone/diethyl ether/water and 2, 4-dinitrofluorobenzene-induced chronic itching and inflammatory pain, were largely attenuated in TLR2 knockout (KO) mice. The TLR2 agonist Pam3CSK4, which targets TLR2/1 heterodimers, evoked pain and itch behavior, whereas lipoteichoic acid (LTA) and zymosan, which recognize TLR2/6 heterodimers, produced only pain response. The TLR2 agonist-induced nociceptive and pruritic behaviors were largely diminished in transient receptor potential vanilloid 1 (TRPV1) and transient receptor potential ankyrin 1 (TRPA1) KO mice. Finally, Pam3Csk4 and zymosan increased the [Ca2 + ]i in DRG neurons from wild-type mice. However, the enhancement of [Ca2 + ]i was largely inhibited in the DRG neurons from TRPV1 and TRPA1 KO mice. Our results demonstrate that TLR2 is involved in different itch and pain behaviors through activating TLR1/TLR2 or TLR6/TLR2 heterodimers via TRPV1 and TRPA1 channels.